Penerapan Strategi Kwl (Know–Want–Learn) Untuk Meningkatkan Hasil Belajar Pendidikan Agama Islam (PAI) Siswa Kelas X SMA IT Unggul Al-Munadi - Aulia Rohmah Nulhaq; Nurman Ginting (EL-EMIR Institute, 2025)
This study focuses on the application of the Know–Want–Learn (KWL) strategy in the context of Islamic Religious Education (PAI) learning at SMA IT Unggul Al-Munadi to improve student achievement. The research employed a Classroom Action Research (CAR) design carried out in two cycles, each consisting of planning, action, observation, and reflection stages. The participants were 32 tenth-grade students. Data were collected using three techniques: learning achievement tests, student activity observations, and documentation. The data were analyzed using Miles & Huberman’s interactive model. The findings revealed a significant improvement in learning outcomes, from 55% in the pre-cycle, increasing to 68% in the first cycle, and reaching 82% in the second cycle, thereby surpassing the school’s Minimum Mastery Criteria (KKM). The KWL strategy also fostered active participation, enhanced students’ ability to ask critical questions, and encouraged reflective learning. These results are consistent with previous studies on the effectiveness of active learning and indicate that KWL has the potential to serve as an innovative approach in Islamic Religious Education.